2000
DOI: 10.1038/35044040
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging of the pores and cages of three-dimensional mesoporous materials

Abstract: Mesostructured composite materials, with features ranging from 20 to 500 A in size, are obtained by the kinetically controlled competitive assembly of organic and inorganic species into nanostructured domains. Short-range order is limited, and long-range order is determined by weak forces such as van der Waals or hydrogen-bonding. Three-dimensional mesoporous materials obtained by removing the organic phase are of particular interest for applications such as catalysis and chemical sensing or separation, for wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
626
0
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 827 publications
(674 citation statements)
references
References 10 publications
40
626
0
8
Order By: Relevance
“…The double gyroid, 24 double diamond, 7 and I-WP 25 structures have all previously been observed in bicontinuous silica-type materials. Table 2 reports structure factors for double gyroid (G), double diamond (D), plumber's nightmare (P), and I-WP structures calculated using the parametric equations of Garstecki and Holyst.…”
Section: I(qθ)mentioning
confidence: 89%
“…The double gyroid, 24 double diamond, 7 and I-WP 25 structures have all previously been observed in bicontinuous silica-type materials. Table 2 reports structure factors for double gyroid (G), double diamond (D), plumber's nightmare (P), and I-WP structures calculated using the parametric equations of Garstecki and Holyst.…”
Section: I(qθ)mentioning
confidence: 89%
“…The relevance of these universal guidelines is as broad as the use of colloids themselves, ranging from photonic bandgap crystals 55,56 to micro-or mesoporous materials used for chemical microreactors and molecular sieves. 57,58 To meet the demands of a particular application, these designer materials must be characterized by a given lattice constant, symmetry, and mechanical properties, and, in the case of porous structures, void size and connectivity. All these parameters can be controlled by tuning the structure and size of the (template) colloidal particles and the interaction between them, and our model establishes a semiquantitative relationship between particle geometry and bulk material properties.…”
Section: Discussionmentioning
confidence: 99%
“…35,37,38 Among these, SBA-16 has three-dimensional (3D) channels and a cubic Im3m (bodycentered cubic arrangement of cages with 8 apertures to the nearest neighbors) structure, which could be more favorable for mass and thermal transfer than a unidirectional pore system. 39 In order to introduce the maximum quantity of metal precursors, as many silanol groups as possible must be retained during the preparation of the silica template. In our previous work, we found that the mesochannels of SBA-15 and KIT-6 were far from completely filled by metal precursors due to a large loss of Si-OH groups during the organic template removal process that involved a thermal calcination, 40,41 and this phenomenon has also been reported by other groups.…”
Section: Introductionmentioning
confidence: 99%